Anagallis Arvensis As A Natural Allelopathic Agent: Effects On Growth Of Zea Mays, Triticum Aestivum, And Pennisetum Glaucum - Ullah, Shakir; Shakir, Lubna; Sohail, Mohammad; Falaknaz, Falaknaz; Ali, Sajid; Subhan, Ghani; khan, Rahid; Dilawar, Naveen (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This study aimed to investigate the allelopathic effects of Anagallis arvensis on Zea mays under controlled laboratory conditions during the period 2022–2024. The aqueous extracts of A. arvensis were tested for their influence on seed germination, seedling growth, fresh weight, and dry weight of Zea mays, Triticum aestivum, and Pennisetum glaucum. Results revealed that a 20 g leaf extract applied for 72 hours significantly inhibited germination percentage, radicle length, fresh weight, and dry weight compared to the control. The degree of inhibition increased with both extract concentration and soaking duration. Treatments with 10 g, 20 g, and 30 g of extract initially enhanced germination over time, with the highest rates observed at 48 hours. However, the 20 g extract caused a notable reduction in germination at this same time point. Overall, a 72-hour treatment duration led to reduced mean germination rates across all concentrations. At lower extract concentrations, extended soaking time had minimal impact on germination. Notably, at 24 hours, germination increased with rising extract concentration; similarly, at 48 hours, germination improved with concentration except at 20 g, where a decline was observed. The only exception to the general trend was an increase in plumule length under the 10 g extract treatment. These findings suggest that the presence of A. arvensis leaf and stem litter in agricultural fields may negatively impact the germination and growth of associated crops, ultimately leading to reduced yield.